Dampak Tidak Adanya Peran AyahTerhadap Perkembangan Anak Di Indonesia - Fatma Ratu Shifa; Asep Suherman (CV. ITTC INDONESIA, 2024)
This study examines the impact of father absence on child development in Indonesia, focusing on its effects on psychological balance and children's rights to adequate care. The primary objective of this research is to explore how the absence of a father figure influences children's psychological, emotional, and social development. The methodology employed is descriptive and explanatory research, analyzing various factors that contribute to the effects of father absence, including social, economic, and environmental conditions. The findings indicate that the absence of a father figure can lead to boys experiencing a crisis of masculinity and difficulties in understanding gender roles, while girls may be at risk of excessive dependency and psychological issues such as anxiety and depression. Although some positive outcomes, such as increased maternal independence, were noted, the negative impacts of father absence are more pronounced and can persist into adulthood, affecting children's ability to form romantic relationships. This research emphasizes the importance of raising awareness about the vital role of fathers in parenting and provides recommendations to support father involvement in families.